The role of roxadustat in chronic kidney disease patients complicated with anemia - Jie Liu; Fan Yang; Yousuf Waheed; Shulin Li; Kun Liu; Xinglei Zhou (The Korean Journal of Internal Medicine, 2023)
The incidence of chronic kidney disease (CKD) is increasing worldwide and the current prevalence rate is 13.4%. There are > 120 million CKD patients in China and this number is expected to increase. One of the main abnormalities in patients with CKD and kidney impairment is decreased synthesis of erythropoietin (EPO), which causes anemia and affects iron metabolism. The probability of developing is higher in anemia patients with CKD than in the general population, and the incidence increases as kidney function decreases. Deficient EPO production by the kidney is the most important cause of renal anemia. Notably, anemia in patients with CKD has multiple causes, such as bleeding caused by platelet dysfunction, iron deficiency due to digestive and absorption disorders of the gastrointestinal tract, and shorter red blood cell life. Anemia is also a leading cause of hospitalization in patients with CKD. A new oral medication to treat renal anemia, the hypoxia-inducible factor prolyl hydroxylase inhibitor called roxadustat (FG-4592), regulates iron metabolism and promotes erythropoiesis. This drug has a therapeutic effect on patients with CKD. Roxadustat showed advantages over EPO in clinical experiments. This review summarizes the mechanisms of action, clinical applications, effectiveness, and safety of roxadustat.